2020
DOI: 10.5194/wes-5-519-2020
|View full text |Cite
|
Sign up to set email alerts
|

Cross-contamination effect on turbulence spectra from Doppler beam swinging wind lidar

Abstract: Abstract. Turbulence velocity spectra are of high importance for the estimation of loads on wind turbines and other built structures, as well as for fitting measured turbulence values to turbulence models. Spectra generated from reconstructed wind vectors of Doppler beam swinging (DBS) wind lidars differ from spectra based on one-point measurements. Profiling wind lidars have several characteristics that cause these deviations, namely cross-contamination between the three velocity components, averaging along t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The FLORIS model is tuned to match the depth of the measured baseline wake losses for SMV5 during the experiment by adjusting the turbulence intensity input, which affects the rates of wake recovery and expansion; we found that when using the "Gauss" velocity model, a turbulence intensity of 11 % represents the overall wake losses during the experiment reasonably well. We treat turbulence intensity as a tuning parameter rather than using the measured turbulence intensity as an input to FLORIS because (1) the turbulence intensity measurements provided by the groundbased and nacelle lidars do not represent traditional turbulence measurements (e.g., from a cup or sonic anemometer) because of volume averaging and line-of-sight measurement limitations (Kelberlau and Mann, 2020) and (2) further work is required to validate the relationship between turbulence intensity and wake deficits (Niayifar and Porté-Agel, 2015) that is used in the GCH model. Last, the power loss suffered as a result of yaw misalignment is modeled in FLORIS by scaling the rotor-averaged wind speed, v avg , used to determine power and thrust as follows:…”
Section: Floris Wind Farm Control Engineering Modelmentioning
confidence: 99%
“…The FLORIS model is tuned to match the depth of the measured baseline wake losses for SMV5 during the experiment by adjusting the turbulence intensity input, which affects the rates of wake recovery and expansion; we found that when using the "Gauss" velocity model, a turbulence intensity of 11 % represents the overall wake losses during the experiment reasonably well. We treat turbulence intensity as a tuning parameter rather than using the measured turbulence intensity as an input to FLORIS because (1) the turbulence intensity measurements provided by the groundbased and nacelle lidars do not represent traditional turbulence measurements (e.g., from a cup or sonic anemometer) because of volume averaging and line-of-sight measurement limitations (Kelberlau and Mann, 2020) and (2) further work is required to validate the relationship between turbulence intensity and wake deficits (Niayifar and Porté-Agel, 2015) that is used in the GCH model. Last, the power loss suffered as a result of yaw misalignment is modeled in FLORIS by scaling the rotor-averaged wind speed, v avg , used to determine power and thrust as follows:…”
Section: Floris Wind Farm Control Engineering Modelmentioning
confidence: 99%
“…Measurements of turbulence by lidars are affected by spatial average filtering effects caused by the lidar probe volume and cross-contamination effects from combining lineof-sight velocities at different locations assuming instantaneous homogeneity and not only statistical homogeneity (Sathe and Mann, 2013;Kelberlau and Mann, 2020). Both effects contribute to the systematic error of turbulence estimation using lidars.…”
Section: Introductionmentioning
confidence: 99%
“…Groundbased wind lidar can be used to provide wind data, but their ability to provide turbulence data that can be used in turbine design is a subject of ongoing research (e.g. Sathe et al, 2011;Clifton et al, 2018;Kelberlau and Mann, 2020).…”
Section: Obtaining Inflow Data To Validate Wind Turbine Aeroelastic M...mentioning
confidence: 99%